A Highly Flexible, Automated System Providing Reliable Sample Preparation in Element- and Structure-Specific Measurements. (October 2016) - Vorberg, Ellen; Fleischer, Heidi; Junginger, Steffen; Liu, Hui; Stoll, Norbert; Thurow, Kerstin
Life science areas require specific sample pretreatment to increase the concentration of the analytes and/or to convert the analytes into an appropriate form for the detection and separation systems. Various workstations are commercially available, allowing for automated biological sample pretreatment. Nevertheless, due to the required temperature, pressure, and volume conditions in typical element and structure-specific measurements, automated platforms are not suitable for analytical processes. Thus, the purpose of the presented investigation was the design, realization, and evaluation of an automated system ensuring high-precision sample preparation for a variety of analytical measurements. The developed system has to enable system adaption and high performance flexibility. Furthermore, the system has to be capable of dealing with the wide range of required vessels simultaneously, allowing for less cost and time-consuming process steps. However, the system's functionality has been confirmed in various validation sequences. Using element-specific measurements, the automated system was up to 25% more precise compared to the manual procedure and as precise as the manual procedure using structure-specific measurements.